(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Upton Sinclair’s select works, including The Jungle (1906), King Coal (1917), Oil! (1927), and The Flivver King (1937), serve as potent critiques of early 20th-century American industrialization, exposing the dehumanizing effects of capitalist exploitation on workers. Through vivid narratives of meatpacking, coal mining, oil booms, and automobile production, Sinclair highlights perilous working conditions, wage suppression, and corporate greed, advocating socialist reforms. This critical study analyzes these reflections, demonstrating how Sinclair’s muckraking journalism transformed public discourse and spurred legislative changes like the 1906 Meat Inspection Act, underscoring literature’s role in social reform.Following a series of tragedies, including his wife Ona being sexually assaulted by her boss, Jurgis is imprisoned. Upon release, he finds his family evicted and later loses his wife, newborn baby, and young son to illness and neglect.Broken and disillusioned, Jurgis becomes a tramp before finding hope in the Socialist movement, which promises to fight for the rights of the working class.Sinclair famously remarked, "I aimed at the public’s heart, and by accident I hit it in the stomach." While he wanted to spark a socialist revolution, the public was most outraged by the descriptions of rotten meat. This outcry directly led to the passage of the 1906 Pure Food and Drug Act.